EFFECT OF PREVIOUS CROP NITROGEN APPLICATION ON YIELD OF FOLLOWING MAIZE UNDER DIFFERENT PLANTING PATTERNS - Y. X. Zhao; X. M. Mao; X. B. Zhou (Journal of Animal and Plant Sciences, 2018)
Nitrogen application could affect the crop growth and yield, and then affect the water use efficiency (WUE) . This study aimed to determine the effects of previous winter wheat (Triticum aestivum L.) nitrogen application and following summer maize ( Zea mays L.) planting pattern on the yield and WUE of maize in the North China Plain. The experiments consisted of the winter wheat 112.5 (N1) and 225.0 ( N2) kg/ha nitrogen application, and summer maize flat planting (FP) and ridge tillage planting (RTP) treatments arranged in a split-plot design ( 4 m × 4 m) with three replications in 2014 and 2015. Results showed that planting pattern and previous crop nitrogen had significant effect on yield components and WUE. Compared with FP, the RTP increased leaf relative water content, soil water content, soil water storage, WUE, and yield by 1.9%, 2.8%, 2.0%, 3.8%, and 7.1%, respectively. The yield, harvest index, stem diameter, and ear diameter of N2 treatment were 13.0%, 11.9%, 5.5%, and 2.3% higher than those of N1, respectively. Nitrogen of the previous winter wheat and the RTP pattern improved the water status and yield component of summer maize. It may be concluded previous crop nitrogen and RTP pattern can improve population structure, increase the yield and WUE of summer maize and thus is a promising method for farmers in North China. Planting patterns and nitrogen application rate
Keywords: NA